Analisis Nilai Karakter pada Cerpen pada Buku Siswa Kelas III SD Tema 8 Praja Muda Karana - Jendriadi, Jendriadi; Fitri, Rahma; Apfani, Sry; Anwar, Rahmi; Oktavia, Mila; Ismira, Ismira; Taufik, Muhammad (Indonesian Research Journal on Education, 2021)
This research is motivated by findings during initial field observations that the majority of teachers donot place too much importance on character values in literature learning in elementary schools. In fact,literary learning is an educational tool that plays a major role in the world of education to shape anddevelop children's personalities. literature plays a role as character building which is believed to have amajor role in the development of character in children so that they are able to develop human beingswho are completely fun from an early age.Short stories, as a part of literary work that will be taught tochildren, actually can be analyzed the character values they have so that the positive energy can betransmitted to children. The purpose of this study was to analyze the character values in the short storiesin the third grade students' book of the theme 8 Praja Muda Karana. The approach used is a qualitativeapproach in the form of analysis of short stories in class III SD books. The subjects of this study were allshort stories contained in the third grade students' book of 8 Praja Muda Karana theme. The shortstories in the third grade students' book of the theme 8 Praja Muda Karana consist of eight short stories.The short story is entitled I am an independent child, independently doing homework, independentduring worship, practicing independently, I like adventure, cycling with friends, being a receptionist,holding charity activities. After being read and analyzed, it was found that there are several charactervalues that can be transmitted to children including: independence, friendly / communicative, religious,tolerance, discipline, hard work, curiosity, love for the country and several other noble characters.